Implementation of lung cancer CT screening in the Nordic countries. (3rd October 2017) - Pedersen, Jesper Holst; Sørensen, Jens Benn; Saghir, Zaigham; Fløtten, Øystein; Brustugun, Odd Terje; Ashraf, Haseem; Strand, Trond-Eirik; Friesland, Signe; Koyi, Hirsh; Ek, Lars; Nyrén, Sven; Bergman, Per; et al.
Abstract: Introduction: We review the current knowledge of CT screening for lung cancer and present an expert-based, joint protocol for the proper implementation of screening in the Nordic countries. Materials and methods: Experts representing all the Nordic countries performed literature review and concensus for a joint protocol for lung cancer screening. Results and discussion: Areas of concern and caution are presented and discussed. We suggest to perform CT screening pilot studies in the Nordic countries in order to gain experience and develop specific and safe protocols for the implementation of such a program.